2018
DOI: 10.1128/msystems.00113-18
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Functional Responses to Cholesterol Catabolism in Denitrifying Sludge

Abstract: Steroids are ubiquitous and abundant natural compounds that display recalcitrance. Biodegradation via sludge communities in wastewater treatment plants is the primary removal process for steroids. To date, compared to studies for aerobic steroid degradation, the knowledge of anaerobic degradation of steroids has been based on only a few model organisms. Due to the increase of anthropogenic impacts, steroid inputs may affect microbial diversity and functioning in ecosystems. Here, we first investigated microbia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 88 publications
0
16
0
Order By: Relevance
“…The genomes of 3 characterized anaerobic estrogen utilizers do not possess a complete set of biosynthetic genes to produce cobalamin for estrogen utilization (31). Interestingly, a previous study on microbial cholesterol catabolism also observed common cobalamin auxotrophy among cholesterol-utilizing anaerobes (33). These findings suggest that 1) the occurrence of interspecies cobalamin transfer between the cobalamin producers and the anaerobic steroid utilizers in natural habitats and 2) estrogens and other steroids are prone to accumulating in O 2 -limited ecosystems devoid of cobalamin or cobalamin-producing microbes.…”
Section: Resultsmentioning
confidence: 99%
“…The genomes of 3 characterized anaerobic estrogen utilizers do not possess a complete set of biosynthetic genes to produce cobalamin for estrogen utilization (31). Interestingly, a previous study on microbial cholesterol catabolism also observed common cobalamin auxotrophy among cholesterol-utilizing anaerobes (33). These findings suggest that 1) the occurrence of interspecies cobalamin transfer between the cobalamin producers and the anaerobic steroid utilizers in natural habitats and 2) estrogens and other steroids are prone to accumulating in O 2 -limited ecosystems devoid of cobalamin or cobalamin-producing microbes.…”
Section: Resultsmentioning
confidence: 99%
“…betaproteobacterial genus [23][24][25]. Moreover, Moreover, several denitrifying bacteria capable of complete steroid degradation have been isolated from steroid-treated mesocosms [26].…”
Section: Discussionmentioning
confidence: 99%
“…For shotgun metagenomic sequencing, the quality of DNA was examined using the Fragment Analyzer (Agilent, USA), and Kapa HyperPrep Kits (Kapa Biosystems, USA) were used for constructing four DNA libraries. The prepared libraries with average fragment size from 451 to 461 bp were sequenced using an Illumina For metatranscriptomic sequencing, the quality of RNA (RNA integrity number from 7.5 to 9.4) was examined using the BioAnalyzer 2100 system with an RNA 6000 Nano Kit (Agilent, USA) before using the Ribo-Zero rRNA removal kit (Illumina) and TruSeq Stranded LT mRNA Library Prep kit v2 as described previously [23]. The four prepared libraries with average fragment size from 328 to 351 bp were sequenced using an Illumina HiSeq 2500 sequencer, yielding 97,486,966 reads for SDN1_day14; 92,150,650 for SDN2_day14; 94,830,584 for SPN1_day7; and 93,982,586 for SPN2_day7.…”
Section: Gas Chromatography (Gc)-ms Analysis Of 2-ethyl-1-hexanolmentioning
confidence: 99%
“…The genetic pathways for the degradation of the stressors were below the detection limits prior to incubation but were afterward identified, with variations across replicates (Wang et al, 2017; Table 1). Further, the catabolism of cholesterol was found to be mediated through the 2,3-seco pathway by rare bacteria from the denitrifying sludge of a wastewater treatment plant (Wei et al, 2018; Table 1). Finally, community-level resistance and degradation of phenols, which are toxic compounds often released into the environment due to industrial activities (Duan et al, 2018), has been as well related with the prokaryotic rare biosphere (Szabó et al, 2007; Table 1).…”
Section: The Prokaryotic Rare Biosphere Responds To Pollutants: Potenmentioning
confidence: 99%